BETWEEN STRUGGLES AND VERSES: MARCH 8TH AS A PATHWAY FOR FEMALE VOICES IN POETRY (Citizenship in Action: Extension and Culture Magazine, 2025)
This Experience Report presents the work of scholarship students from the Programa de Residencia Pedagógica of the Letters course at the Faculdade de Ciências e Letras de Iguatu (UECE/FECLI), during an activity carried out at the Filgueiras Lima Full-Time High School in Iguatu, Ceará. The proposal aimed to connect International Women's Day and World Poetry Day through a poetry recital that encouraged the reading and listening of poems written by Brazilian women authors. The activity fostered students’ contact with female literary voices, expanded their literary repertoire, and stimulated aesthetic sensitivity, while also encouraging critical reflection on gender issues, identity, empowerment, and social justice. Based on the studies of Cosson (2018, 2021), Pinheiro (2018), Duarte (2003), and the guidelines of the Brazilian National Common Curricular Base (2018), we understand literature as a formative, artistic, and political practice—capable of shaping more critical, conscious, and empathetic individuals. The literary event became a space of belonging, expression, and dialogue, strengthening students’ intellectual autonomy and bringing art closer to the school environment as a tool for transformation. This experience reinforces the importance of promoting poetry reading, especially poetry written by women, in the school context, pointing to paths toward a more sensitive, plural, and humanizing education. We hope it may serve as inspiration for other pedagogical practices committed to equity and literary sensitivity.